Implementasi Model Pembelajaran Inklusif Untuk Anak Slow Learner - Rafael Lisinus Ginting; Kenanga Natalia Ayu Sari BR Sipayung; Dea Ramahdani; Muthiah zhafirah; Gracia Hutasoit; Dewi Ramadana; Inggrid Caroline; Azzah Jihan Zafirah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Slow learner children experience learning and behavior problems. This is because children have limited intellectual abilities and psychological skills. The aim of this research is to provide a solution to increase the interest and motivation to learn in slow learner children by using game therapy. The type of research used by the author is literature study. Where, the literature study method is a series of activities relating to methods of collecting library data, reading and taking notes, and managing research materials. Because the data collected is in the form of words or descriptions, the research uses a qualitative approach. Based on several research results, it shows that slow learner children experience learning and behavioral problems. This is because children have limited intellectual abilities and psychological skills. Slow learner children also experience difficulty concentrating, get bored easily, so children tend to have a lot of undirected activities. Apart from learning problems, slow learner children also face behavioral problems. It is hoped that Indonesian society, especially educators, will respond and educate children with special needs well and according to expectations.